Optimizing R&D to Enhance Local Content (TKDN) in Electric Motor Components for National Industry Independence - pudimirama herman; Hendra; Hamdan Akbar Notonegoro; Reski Septiana; Rispandi (METAL: Jurnal Sistem Mekanik dan Termal, 2025)
The electric motor industry in Indonesia is a strategic sector that plays a vital role in supporting national economic development. However, challenges in improving competitiveness—particularly regarding the use of local components—remain a major obstacle. Therefore, strengthening the Domestic Component Level (TKDN) is essential as an effort to increase industrial self-reliance, strengthen the local economy, and reduce dependence on imports [1].This study aims to calculate and analyze the TKDN component level of electric motor products and evaluate its impact on the development of local industries and national economic growth. Furthermore, the study seeks to provide strategic recommendations for sustainably increasing TKDN in the future. The research methods include literature review, regulatory analysis, and the collection and analysis of primary data from relevant industry stakeholders. This research adopts a case study approach focused on the automotive sector, with emphasis on actual conditions in Indonesia, referring to Government Regulation No. 28 of 2024. The expected outcomes include: (1) a documented TKDN component level calculation, and (2) policy recommendations for enhancing TKDN that support the development of local technology. It is expected that the results of this study will encourage national industrial independence, expand employment opportunities, and enhance the global competitiveness of locally produced goods.